2015
DOI: 10.1017/s136898001500049x
|View full text |Cite
|
Sign up to set email alerts
|

Trans-fatty acids in cooking oils in Bogota, Colombia: changes in the food supply from 2008 to 2013

Abstract: Objective: Long-chain n-3 fatty acid intake in Colombia is low because fish consumption is limited. Vegetable oils with high n-3 fatty acid content are recommended, but their concentrations of trans fats were high in previous studies. Thus, regular monitoring of the fatty acid composition of vegetable oils is required. Our objective was to quantify the fatty acid composition in commercially available oils in Bogota, Colombia and determine if composition changed from 2008 to 2013. Design: Cross-sectional study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
4
1
0
5
Order By: Relevance
“…We also found that cooking oil usage predicted LCPUFA status, despite the low levels of preformed LCPUFA typically found in vegetable oils. [38][39][40] This is in line with the results of an intervention study among Colombian families in which soybean or sunflower oil increased whole blood LCPUFA in school-aged children. 14 In our study, canola oil users had among the highest levels of both n-6 and n-3 LCPUFA, despite not having the highest levels of LA and ALA; this could reflect greater conversion of essential PUFA into LCPUFA.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also found that cooking oil usage predicted LCPUFA status, despite the low levels of preformed LCPUFA typically found in vegetable oils. [38][39][40] This is in line with the results of an intervention study among Colombian families in which soybean or sunflower oil increased whole blood LCPUFA in school-aged children. 14 In our study, canola oil users had among the highest levels of both n-6 and n-3 LCPUFA, despite not having the highest levels of LA and ALA; this could reflect greater conversion of essential PUFA into LCPUFA.…”
Section: Discussionsupporting
confidence: 82%
“…Some of the associations between specific oils and essential PUFA are expected according to the fatty acid composition of cooking oils in Latin American countries. [38][39][40] Soybean and canola oils are high in ALA, whereas palm oil is low in all n-6 and n-3 PUFA; correspondingly, in our study soybean and canola oil users had among the highest ALA levels, whereas palm oil users had among the lowest levels of all PUFA. The LA content is highest in corn and sunflower oils, [38][39][40] but we observed the highest adipose LA FA% among users of soybean oil.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…<2 % of total fat) (45) . Thus, more work is needed to achieve the WHO recommendation of eliminating trans fats due to their harmful health effect and it is likely that banning the use of PHO would result in a further reduction of TFA, as seen in other countries where similar approaches have been taken (17,33,(74)(75)(76)(77) . Our results also highlight that monitoring the prevalence of HO and their TFA content in foods remains critical to assess unintended consequences, such as substantially higher levels of TFA in foods exceeding recommendations, a phenomenon observed in the present study, and particularly as the current labelling regulations do not require to differentiate between levels of hydrogenation (64) .…”
Section: Discussionmentioning
confidence: 99%
“…Entre las grasas trans industrializadas se encuentran las adicionadas a los comestibles ultraprocesados, las comidas rápidas, los empaquetados y los aceites de origen vegetal, que frecuentemente se usan para la preparación de diversos alimentos y que para el caso de Colombia, en su mayoría, presentan concentraciones superiores en un 2 % a los recomendados por la Organización Panamericana de la Salud (16). Sin embargo, dada la descripción de los efectos perjudiciales que tiene sobre la salud el consumo de este tipo de grasas, el perfil nutricional de los aceites comercializados en grandes superficies ha presentado una mejoría significativa, con una reducción importante en las cantidades de grasas trans.…”
Section: Grasas Transunclassified